A Letter to My Friend and Chaplain Colleague Imam Sohaib Sultan, Zichrono Livracha (of Blessed Memory) - Zoosman, Cantor Michael J. (Journal of pastoral care & counseling, 2024)
I am a Jewish chaplain and I felt moved to write this letter to my esteemed colleague Imam Sohaib Sultan, of blessed memory. Sohaib and I each experienced our first unit of Clinical Pastoral Education together as part of the same cohort in the summer of 2008. Sohaib died tragically in 2021. Here, I reflect on how we might respond to the current Israel-Hamas War.